Marketing weights and ultrasonic measurements of loin eye muscle in Karya lambs - YARALI, ENGIN; YILMAZ, ONUR (The Indian Journal of Animal Sciences, 2014)
The objective of this study was to determine of longissimus dorsi muscle (loin eye muscle) properties which are closely related to meat yield and meat quality in Karya lambs. Karya lambs (36) were used. The longissimus dorsi muscle (loin eye muscle) area width, depth and backfat depth were measured ultrasonically of the cross sectional area between the 12th and 13th ribs in market period and also at this time lamb live weight were recorded. Least square means for ultrasonic measurements of eye muscle depth, width, area and backfat depth were 2.18 cm, 4.14 cm, 6.41 cm2 and 0.08 cm, respectively. The correlations between lamb live weight with eye muscle depth and eye muscle area were found important.